Analisis Perbandingan Pola Migrasi dan Proyeksi Penduduk sebagai Dasar Perencanaan Pembangunan Wilayah di Provinsi Gorontalo - Fery Rahmat Angriawan Bagu; Fitriyane Lihawa; Iswan Dunggio (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to analyze and compare migration data with the population growth projections of Gorontalo Province for the 2020–2035 period. A descriptive quantitative approach was used to evaluate in- and out-migration patterns based on the 2020 Long Form Population Census and BPS population projections. The findings reveal regional migration disparities, with Gorontalo City and Bone Bolango Regency experiencing positive net migration, while Pohuwato and Boalemo show high out-migration rates. Meanwhile, the demographic projections indicate an increasing dependency ratio and a significant growth in the elderly population. The combination of migration dynamics and demographic trends affects the age structure and regional capacity to support sustainable development. These findings provide an essential basis for evidence-based migration policy formulation to reduce regional disparities and strengthen local economic development.